2003
DOI: 10.1038/sj.bjc.6601380
|View full text |Cite
|
Sign up to set email alerts
|

Asking questions can help: development and preliminary evaluation of a question prompt list for palliative care patients

Abstract: Question prompt lists (QPLs) have been shown to be an inexpensive and effective communication tool for patients in oncology consultations. We aimed to develop and pilot a QPL for palliative care (PC) patients. In order to identify suitable questions for inclusion in the QPL, we conducted focus groups and individual interviews with 19 patients, 24 carers and 22 PC health professionals. A further 21 health professionals reviewed the draft document. The draft QPL was piloted in 23 patients. In total, 112 question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 17 publications
3
148
0
2
Order By: Relevance
“…[13] QPLs have been developed for patients seeing medical oncologists, radiation oncologists or surgeons for the first time, [14,15] and patients and carers newly referred to palliative care. [16] No QPL has been developed for patients with advanced cancer outside the palliative care setting. Such patients newly face deterioration and eventual death, experiencing challenges in eliciting and adapting to information about prognosis and endof-life issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] QPLs have been developed for patients seeing medical oncologists, radiation oncologists or surgeons for the first time, [14,15] and patients and carers newly referred to palliative care. [16] No QPL has been developed for patients with advanced cancer outside the palliative care setting. Such patients newly face deterioration and eventual death, experiencing challenges in eliciting and adapting to information about prognosis and endof-life issues.…”
Section: Introductionmentioning
confidence: 99%
“…As they remain well enough to participate in Advance Care Planning (ACP), from authors. [14][15][16][21][22][23][24] Where possible, items were adapted from existing QPLs if they focussed on issues relevant for the target population and purpose of the QPL including; prognosis, treatment options and decisions with non-curative intent, end-of-life issues, ACP and supportive or palliative care services for the patient, carer or family.…”
Section: Introductionmentioning
confidence: 99%
“…14 Clayton et al developed a 20-page, 112-item QPS for palliative care patients by conducting focus groups and individual interviews in 19 patients, 24 caregivers, and 22 palliative care physicians, followed by a pilot study on 23 patients. 16 They found that participants perceived the QPS as useful in their communication with their doctors. We used this study as the basis for the development of our prompt sheet since it was thoroughly conducted with the participation of healthcare professionals, patients, and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the pilot study that followed the QPS development, patients and caregivers perceived those end-of-life questions as helpful in facilitating hitherto difficult discussions regarding the topic and readily endorsed them. 16 The expert panel consisted of members with great experience in caring for patients with advanced cancer and hence were well equipped to provide the most needed information for the development of the QPS (Table 1). When panel members have an in-depth knowledge of the topic under investigation, this greatly enhances content validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation